2001
DOI: 10.1042/0264-6021:3570859
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-resistance P-glycoprotein (MDR1) secretes platelet-activating factor

Abstract: The human multidrug-resistance (MDR1) P-glycoprotein (Pgp) is an ATP-binding-cassette transporter (ABCB1) that is ubiquitously expressed. Often its concentration is high in the plasma membrane of cancer cells, where it causes multidrug resistance by pumping lipophilic drugs out of the cell. In addition, MDR1 Pgp can transport analogues of membrane lipids with shortened acyl chains across the plasma membrane. We studied a role for MDR1 Pgp in transport to the cell surface of the signal-transduction molecule pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 44 publications
0
36
0
Order By: Relevance
“…Although never fully elucidated, possible P-gp substrates responsible for this effect on migration could include PAF or S1P (Table II) [8,23]. The same group later reported MRP1 expression on both mouse and human DCs, with considerably higher expression levels in mice, and showed that DC migration was hampered in mice lacking Mrp1 expression [7].…”
Section: Migrationmentioning
confidence: 94%
See 2 more Smart Citations
“…Although never fully elucidated, possible P-gp substrates responsible for this effect on migration could include PAF or S1P (Table II) [8,23]. The same group later reported MRP1 expression on both mouse and human DCs, with considerably higher expression levels in mice, and showed that DC migration was hampered in mice lacking Mrp1 expression [7].…”
Section: Migrationmentioning
confidence: 94%
“…Several ABC transporters have been recognized for their roles in generating clinical multidrug resistance of tumor cells owing to their ability to remove various cytostatic drugs from tumor cells ( Figure Ia), thereby reducing the intracellular drug load and preventing tumor cell killing [1,3,4]. ABC transporters are expressed on immune cells such as DCs and immune regulatory molecules have been identified as physiological ABC transporter substrates [6,7,9,10,23,25,26,69], which prompted a model whereby substrate secretion can result in autocrine or paracrine induction of intracellular signaling, leading to cell differentiation and migration ( Figure Ib) [12]. Polymorphisms have been reported in ABC transporter genes, which could affect their substrate specificity [70].…”
Section: Mdr-related Abc Transportersmentioning
confidence: 99%
See 1 more Smart Citation
“…First hints for a role of some family members in 2914 T. Pomorski and A. K. Menon Lipid flippases and their biological functions the outward movement of lipids across the PM came from the finding that PC secretion into mouse bile required ABCB4 [108] and that this liver transporter enhanced transport of newly synthesized PC to the surface of transgenic fibroblasts [109]. In studies on short chain lipids, human ABCB4 was found to be specific for PC, whereas, unexpectedly, the closely related multidrug transporter ABCB1 translocated a wide variety of short chain lipids [110][111][112][113], including the short chain PC platelet-activating factor [114,115]. The glutathione-dependent multidrug transporter ABCC1 transported short-chain PC, PS, sphingomyelin, and glucosylceramide analogs and has been suggested to maintain the outward orientation of natural choline phospholipids to the PM [116][117][118][119].…”
Section: Abc Transporters: Energy-dependent Outward Lipid Flippases Omentioning
confidence: 99%
“…Several studies have indicated roles for P-gp in lipid transport, intracellular trafficking of cholesterol, cell death, cell differentiation, and immune responses (16,17). Regarding the last, P-gp was shown to exhibit immunomodulatory activity and to influence the secretion of various inflammatory mediators, such as steroids, prostaglandins, platelet-activating factor, and cytokines (13,(18)(19)(20)(21). Specifically, it was demonstrated that P-gp mediates the secretion of interleukin 2 (IL-2), IL-4, tumor necrosis factor alpha (TNF-␣), and gamma interferon (IFN-␥) in T lymphocytes (19,22,23) and of cytotoxic compounds in NK cells (24).…”
mentioning
confidence: 99%